The Mediating Role of Technological Capability between Social Media Marketing and MSMEs Performance - Herman, Hendri; Ocak, Altug (ICON Publisher, 2025)
The aim of this study is to determine the effect of social media marketing towards MSMEs performance. The sample size used in this research was 135 MSMEs respondents. The sample was accessed through an online survey questionnaire. Smart PLS 3.0 is utilized in analysis within this study. The findings show that social media marketing has a positive effect on MSMEs performance and technological capability. Technological ability has a positive effect on MSMEs performance and acts as a mediator between social media marketing and MSMEs performance. The limitation of the study is that it was conducted in one geographical area, limiting generalizability to other industries or other regions with varied characteristics. The paper contributes to the body of literature by empirically validating technological ability as a mediator variable between social media marketing and MSMEs performance. These results suggest that MSME managers should invest in social media for both marketing and internal capacity building, put in place technology monitoring systems, and technology alliances with external organizations. Future research is also suggested to test other mediating or moderating variables like technological innovations, market forces, or organizational designs.